Current approach to diagnosis and management of osteoarthritis - Claudia Ickinger; Mohammed Tikly (South African Family Practice)
Osteoarthritis (OA) is a common chronic degenerative joint disorder and a major cause of pain and disability, especially in the elderly. The prevalence is steadily rising due to an increase in life expectancy and certain lifestyle factors. OA is a complex dynamic process involving all tissues of the joint organ. Multiple risk factors are associated with the occurrence and progression of OA. There is extreme variability in presentation at different joint sites and between individuals. Management of OA involves a comprehensive approach consisting of preventative measures and numerous therapeutic modalities which should be tailored to individual needs. The family practitioner plays a vital role in the diagnosis of OA, the initiation of treatment and the ongoing monitoring of the condition.